Chemical Constituent of Acacia auriculiformis Wood Extractives and Their Antioxidant Activity - Yanico Hadi Prayogo; Irmanida Batubara; Rita Kartika Sari; Kosei Yamauchi; Tohru Mitsunaga; Wasrin Syafii; Saat Egra (Jurnal Sylva Lestari, 2023)
Acacia auriculiformis showed good potential to be developed as a raw material for bioactive compounds. The heartwood of A. auriculiformis is still rarely explored. The purpose of this study was to identify the bioactive components of the heartwood. Six compounds were identified from the heartwood through nuclear magnetic resonance and mass spectroscopy, namely the C-3,4',7,8 hydroxyl substituted flavonoids and chalcone. Two methylated teracacidins and chalcone-like teracacidin were identified for the first time in the A. auriculiformis heartwood, along with three known compounds. These compounds showed good radical scavenging and reduction activity, compared to crude extract and ascorbic acid, using three different antioxidant assays. The molecular structure-dependent activity was observed to affect the trend of the different antioxidant activities. This finding shows good potential for further development of plant parts of A. auriculiformis from Indonesia as new raw materials for medicines. Keywords: Acacia auriculiformis, antioxidant, chalcone, flavonoid, heartwood